Nicotinamide Mononucleotide Combined With Lactobacillus fermentum TKSN041 Reduces the Photoaging Damage in Murine Skin by Activating AMPK Signaling Pathway - Zhou, Xianrong; Du, Hang-Hang; Ni, Luyao; Ran, Jie; Hu, Jian; Yu, Jianjun; Zhao, Xin (Frontiers in Pharmacology, 2021)
Long-term exposure to UVB (280–320 nm) can cause oxidative skin damage, inflammatory injury, and skin cancer. Research on nicotinamide mononucleotide (NMN) and lactic acid bacteria (LAB) with regard to antioxidation, anti-inflammation, and prevention of other age-related diseases has received increasing attention. In the present study, the in vitro antioxidant analysis showed that NMN combined with L. fermentum N4-1 has a high scavenging ability on OH, ABTS and DPPH free radicals, and it also possess a good total antioxidant capacity. The animal experimental results show that NMN combined with LAB maintained normal liver morphology of mice and reduced pathological damage to murine skin. NMN combined with LAB significantly increased the serum levels of total superoxide dismutase (T-SOD), catalase (CAT), and interleukin (IL)-10, but reduced the levels of malondialdehyde, advanced glycation end products, tumor necrosis factor (TNF)-α, and IL-6. NMN combined with LAB increased T-SOD, CAT, IL-10, Na+-K+-ATPase, and NAD+ levels in the skin, but reduced TNF-α level in the skin. NMN combined with LAB increased the mRNA expression levels of SOD1, CAT, glutathione, IκB-α, IL-10, AMP-activated protein kinase (AMPK), liver kinase B1, peroxisome proliferator-activated receptor γ co-activator-1α, and forkhead transcription factor O in the skin and liver, but decreased the mRNA expression levels of nuclear factor (NF)-κBp65, TNF-α, IL-6, and mTOR. NMN combined with LAB increased the protein expression levels of AMPK, IκB-α, SOD1, and CAT in the skin tissues and reduced protein expression of NF-κBp65. NMN combined with L. fermentum N4-1 improved murine skin damage caused by UVB irradiation, and the protective mechanism may be related to activation of the AMPK signaling pathway. The results of this study are expected to provide a reference for preventing and the treating skin photoaging.